2015
DOI: 10.1103/physrevlett.114.090201
|View full text |Cite
|
Sign up to set email alerts
|

Particle Statistics Affects Quantum Decay and Fano Interference

Abstract: Fano resonances and bound states with energy in the continuum are ubiquitous phenomena in different areas of physics. Observations, however, have been limited so far to single-particle processes. In this work we experimentally investigate the multi-particle case and observe Fano interference in a non-interacting two-particle Fano-Anderson model by considering propagation of two-photon states in engineered photonic lattices. We demonstrate that the quantum statistics of the particles, either bosonic or fermioni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 42 publications
2
77
0
Order By: Relevance
“…[92], the models studied in this work may not be so distant from what can be achieved in the laboratory. Along similar lines, one could also consider a many-body extension of the present work [71,72,93].…”
Section: Discussionmentioning
confidence: 99%
“…[92], the models studied in this work may not be so distant from what can be achieved in the laboratory. Along similar lines, one could also consider a many-body extension of the present work [71,72,93].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed that the light intensity may act as another tuning parameter in nonlinear materials, which may enable robust BICs 248 , tunable channel dropping 249 , light storage and release 250,251 , and frequency comb generation 252 . Finally, it was shown that particle statistics can be used to modify some properties of BICs 253 .…”
Section: Discussionmentioning
confidence: 99%
“…If photons can be employed to study the second-order interference of fermions, it will become easier to understand the second-order coherence of fermions. Entangled photon pairs have been employed to simulate the second-order interference of fermions [24][25][26][27][28][29][30]. Special attention is needed to employ entangled photon pairs to simulate the interference of fermions since only antisymmetrical state is possible [24].…”
Section: Introductionmentioning
confidence: 99%